Multilevel Analysis on the Contextual Effect of Posyandu on Exclusive Breastfeeding in Sleman, Yogyakarta - Lestari, Esti; Pamungkasari, Eti Poncorini; Dewi, Yulia Lanti Retno (Journal of Maternal and Child Health, 2019)
Background: There is a piece of increasing evidence that exclusive breastfeeding (EBF) up to six-month of age has important consequences on health and nutritional outcomes of children. However, studies on the contextual effect of integrated health post (posyandu) on EBF are scarce. The purpose of this study was to examine the contextual effect of posyandu on exclusive breastfeeding using multilevel analysis.Subjects and Method: A cross-sectional study was conducted in Sleman, Yogyakarta, from November to December 2018. A sample of 200 lactating mothers was selected by simple random sampling. The dependent variable was exclusive breastfeeding. The independent variables were knowledge, education, age, parity, birth spacing, employment, and family support. The data were collected by a multilevel logistic regression.Results: Exclusive breastfeeding increased with good knowledge (b= 2.66; 95% CI= 0.85 to 4.47; p= 0.004), high education (b= 2.10; 95% CI= 0.29 to 3.91; p= 0.023), maternal age 20-35 years (b= 3.35; 95% CI= 1.46 to 5.24; p<0.001), multiparous (b= 2.90; 95% CI= 0.41 to 3.39; p= 0.012), birth spacing ≥2 years (b= 2.91; 95% CI= 0.92 to 4.89; p= 0.004), unemployed mother (b= 4.53; 95% CI= 2.39 to 6.67; p<0.001), strong family support (b= 2.88; 95% CI= 1.04 to 4.72; p= 0.002). Integrated health post had substantial contextual effect on exclusive breastfeeding with ICC= 29.2%.Conclusion: Exclusive breastfeeding increases with high knowledge, high education, maternal age 20-35 years, multiparous, birth spacing, unemployed mother, strong family support. Integrated health post has the substantial contextual effect on exclusive breastfeeding.Keywords: exclusive breastfeeding, integrated health post, multilevel analysisCorrespondence: Esti Lestari. Masters Program in Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: estylestary727@gmail.com. Mobile: 082363242993.Journal of Maternal and Child Health, 2019, 4(4): 250-259https://doi.org/10.26911/thejmch.2019.04.04.04